Methodology for Structural Analysis of Polysaccharides - Guo, Qingbin; Ai, Lianzhong; Cui, Steve; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
Written by an academic and industry insider, this book provides an informed study on polysaccharide structural analysis and characterization. Specifically focused on analytical techniques, methodologies, and interpretation of data, featured topics include: monosaccharide composition; methylation analysis; 1D & 2D NMR (Nuclear Magnetic Resonance) and MALDI-TOF- (MS) Mas spectrometry. This book is aimed at advanced undergraduates, academic and industrial researchers and professionals studying or using biobased polymers.
Methodologies for extraction, purification and fractionation -- Monosaccharide Composition: acid hydrolysis and chromatography -- Linkage Pattern: Methylation Analysis-GC MS -- Partial Hydrolysis: weak acid hydrolysis and enzymatic hydrolysis -- Mass Spectroscopy of Oligosaccharides (Maldi-TOF) -- 2D NMR spectroscopy and Polysaccharide Structure.
Keywords: Materials -- Analysis; Polymers; Biomaterials; Energy storage; Food science; Characterization and Analytical Technique; Polymers; Biomaterials; Mechanical and Thermal Energy Storage; Food Science